Development of Highly Sensitive and Stable SAW-based Temperature Sensor Array and its Interface Electronics for Realtime Monitoring of Wafer Surface Temperature in Plasma Chamber - Lee, Hyunho; Kim, Sihyeok; Jung, Sangwon; Lee, Keekeun (Journal of Electrical Engineering and Technology, 2024)
Temperature sensor array and its associated peripheral interface electronics has been developed for real-time monitoring of the wafer surface temperature at multiple spots on wafer in the plasma chamber. The developed sensor system comprises multiple surface acoustic wave (SAW) temperature sensors and their associated oscillators inside the chamber, and multiplexer, mixer, low pass filter, comparator, field-programmable gate array, and PC outside the chamber. The interface electronics were assembled on a single printed circuit board to improve the system performance and facilitate the installation of the system. All the SAW temperature sensors on the wafer surface have the same configurations including the same center frequency and the same variations in the resonant frequency with temperature. A multiplexer with several channels was developed to separate the sensor’s signals and then display each sensor signal on PC one by one through a time interval of 0.2 s. The increases in temperature on wafer surface downshifted the resonant frequencies of the SAW temperature sensors. The resultant sensitivity and linearity of the wired temperature sensor system were 24.2 kHz/°C and 0.99, respectively. A wireless wafer temperature measurement was also developed by putting antennas on the output port of the multiplexer and the input port of the mixer. A clear and noticeable frequency shifts were observed on PC display depending on different temperatures at the reading distance of 5 m. The evaluated sensitivity and the linearity were almost the same as those obtained by the wired measurement. The developed SAW sensors showed long term stability against energetic UV-C radiation and electromagnetic interference owing to a thin Si3N4 protection layer.
Keywords: Plasma chambers; Sensor interface; Surface acoustic waves; Surface temperatures; Wafer surface; Wafer surface temperature; Wired and wireless; Wired and wireless sensor interface; Wired sensors; Wireless sensor; Plasma chamber; Surface acoustic wave; Temperature sensor; Wafer surface temperature; Wired and wireless sensor interface